The Reasons Behind Long-Term Endemicity of Brucellosis in Low and Middle-Income Countries: Challenges and Future Perspectives - Samadi, Assadullah; Amiri, Mirwais; Hailat, Nabil (Current microbiology, 2024)
Brucellosis is a neglected worldwide zoonotic disease with more than 500,000 new human cases each year. Direct contact with infected animals and consumption of undercooked animal origin foods are the main routes of brucellosis transmission to humans. Although long endeavor has been applied to control and eliminate brucellosis from animal and human populations in developing countries especially in low- and middle-income countries (LMICs), the disease is still endemic in these regions. Many common or unique factors including raw milk consumption, unhygienic slaughter of livestock, extensive husbandry, budgetary limitations, misdiagnosis, and other conditions play a role in long-term endemicity of brucellosis in these locations. It has been shown that One Health is the only practical approach to control brucellosis; however, applying such methods is challenging in low-resource areas. In such conditions, brucellosis is continuously maintained in animals and repeatedly spread to human populations. In this article, factors playing a critical role in brucellosis endemicity, and the real conditions challenging the application of One Health approach in control of brucellosis are highlighted.